Spectroscopic Study for Resonance Effects on the Carbonyl Double Bond Order in Urea Schiff Bases Which Contain Conjugated System - Baghdad Science Journal (مجلة بغداد للعلوم)
In this work we prepared some schiff bases by condensation urea and benzaldehyde or its derevative ( bromo benzaldehyde or hydroxy benzaldehyde ) as ( 1 : 1 ) mole ( urea : benzaldehyde or its substitution ) to prepare compounds ( A1 , B1 , C1 , D1 , E1 , F1 , G1 ) and ( 1 : 2 ) mole ( urea : benzaldehyde or its substitution ) to prepare compounds ( A2 , B2 , C2 , D2 , E1 , F2 , G2 ) . The prepared compounds identified spectroscopic by infrared spectroscopy FT-IR and Thin layer chromotography T.L.C . The force constant calculated from the wave number for the carbonyl stretching from FT-IR chart and by using the following equation K = 4?2C2?'2? The change in double bond order for carbonyl deteremined in according with some past research by compare the force constant for the prepared compounds with the force constant in past research and calculated bond order statistically by extract the curve equation and calculated the bond order by application curve equation .